Computer-aided design/engineering (CAD/CAE) techniques and their applications. - Leondes, Cornelius T. (Control and dynamic systems, 1993)
Control and Dynamic Systems V59: Computer-Aided Design/Engineering (Cad/Cae) Techniques And Their Applications Part 2 of 2.